2016
DOI: 10.1021/acs.orglett.6b00272
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Oxysulfenylation of Enolates with Sodium Sulfinates: A Strategy To Construct Sulfenylated Cyclic Ethers

Abstract: A new copper-catalyzed oxysulfenylation reaction of enolates with sodium sulfinates has been disclosed. A series of sulfenylated heterocycles including four- and seven-membered cyclic ether were obtained in mild to good yields. This reaction is proposed to go through a radical process, and the sulfur radical (RS(•)) may be a reactive species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 55 publications
0
29
0
1
Order By: Relevance
“…We screened different reductants such as Na 2 SO 3 , Na 2 S and (C 2 H 5 O) 2 POH, and found that they were less efficient ( table 1 , entries 2–4). Without the reductant, the yield was increased up to 82% due to DMF being a reductive solvent [ 41 ] ( table 1 , entry 5). Other additives such as bases (Na 2 CO 3 , NaOH) or acids (HOAc, TsOH) adversely affected the reaction ( table 1 , entries 6–9).…”
Section: Introductionmentioning
confidence: 99%
“…We screened different reductants such as Na 2 SO 3 , Na 2 S and (C 2 H 5 O) 2 POH, and found that they were less efficient ( table 1 , entries 2–4). Without the reductant, the yield was increased up to 82% due to DMF being a reductive solvent [ 41 ] ( table 1 , entry 5). Other additives such as bases (Na 2 CO 3 , NaOH) or acids (HOAc, TsOH) adversely affected the reaction ( table 1 , entries 6–9).…”
Section: Introductionmentioning
confidence: 99%
“…Also a radical process can take place in this new reaction media (Table ), affording the corresponding disulfide (entries 1 and 2). If a hydroxy‐functionalized alkene is added, the double bond reacts with the radical thiol with a subsequent cyclization to afford products 8 c – 8 e (entries 3–5) . Another radical‐mediated reaction is the synthesis of 8 f from phenylpropiolic acid catalysed by phosphoric acid …”
Section: Methodsmentioning
confidence: 99%
“…Based on previously reported studies and these experimental results, a plausible mechanistic pathway is presented in Scheme for the formation of 3a and 5a through the sulfanylation reaction . The reaction is first initiated by Cu(I)‐catalyzed aerobic oxidation to give intermediates thiosulfonate 6 and disulfide 7 via intermediates 8 and 9 through redox decomposition . The copper catalyst then reacts with 6 or 7 to form copper(III) complex 10 , which undergoes DABCO‐mediated transmetallation at the 3‐position of 4‐hydroxycoumarins or 4‐hydroxyquinolinones to form another intermediate copper(III) complex 11 .…”
Section: Methodsmentioning
confidence: 99%